Do Self-Compassion Factors Affect Value-Based Behavior Promotion for Adolescents? The Context of Behavioral Activation - Takagaki, Koki; Yokoyama, Satoshi; Kambara, Kohei (Frontiers in Psychology, 2021)
Behavioral activation has been shown to engender improvement of depressive symptoms. Behavioral activation specifically addresses behavioral patterns that maintain depressive symptoms and increases activation of rewarding behaviors based on a person’s own values. Nevertheless, behaving according to those values can be difficult. Consequently, discussing reduction of barriers to activation of value-based behaviors is important. Self-compassion might promote value-based behavior when a person confronts some obstacle. We evaluated differences in self-compassion and behavioral characteristics at high and low levels of value-based behaviors. Furthermore, we examined relations of self-compassion to value-based behaviors while considering activation, avoidance, and positive reinforcement in the context of behavioral activation. All 800 university student participants (415 women, 385 men; mean age = 20.47 yr; age range 18–24 yr) in this study completed assessments. Descriptive statistics, MANOVA, and stepwise regression analysis relations elucidated their value-based behavior, self-compassion, and behavioral characteristics. Results suggest that participants who behaved according to values had high levels of self-kindness, common humanity, and mindfulness. Results of stepwise regression analyses suggest as a new finding that positive components of self-compassion (self-kindness, common humanity, and mindfulness) are related to value-based behaviors even when behavioral factors are considered in the context of behavioral activation.